Aplikasi administrasi pendidikan sebuah tinjauan filosofis dalam terminologi Kontemporer - Sudin, Mokhtaridi (Institut Agama Islam Negeri (IAIN) Metro, 2014)
Administration is currently a new disciplined that needs to be redefined in term or its application within the education field. Viewed from historical perspective, administration has been rarely contributing to the education field itself. It is especially so when it is compared with other disciplines such as curriculum and philosophy. Nevertheless, there are several points within the concept of administration to be redefined philosophically in term of its ontological, epistemological, and axiological aspects. In comparing the implementation of administration and the purpose of the education as well as the human resource, one cannot ignore, then, the importance of education administration. It is because administration aspect is a part of the whole system within the education itself. Philosophically it can be stated that the education field needs a good administration aspect. The result of education is partly because of its good administration.